THE COHESION OF READING TEXT “ ENGLISH IN FOCUS” FOR THE YEAR SEVEN JUNIOR HIGH SCHOOL PUBLISHED BY DEPARTEMEN PENDIDIKAN NASIONAL (RETAIN, 2014)
THE COHESION OF READING TEXT “ ENGLISH IN FOCUS” FOR THE YEAR SEVEN JUNIOR HIGH SCHOOL PUBLISHED BY DEPARTEMEN PENDIDIKAN NASIONAL Marshalita Siri Valentine S1- English Education, Language and Art Faculty, Surabaya State University dan samiraval@gmail.com Drs. Aswandi, M.Pd S1- English Education, Language and Art Faculty, Surabaya State University Abstrak Tujuan penelitian ini adalah untuk mendeskripsikan kohesi yang ada di materi reading dalam buku pelajaran English in Focus untuk kelas VII Sekolah Menengah Pertama, baik grammatical cohesion maupun lexical cohesion. Penelitian ini menggunakan metode penelitian deskriptif kualitatif dimana hasil penelitian dideskripsikan dalam bentuk kata atau kalimat Hasil penelitian menunjukkan bahwa materi reading di buku English in Focus telah mengaplikasikan semua kohesi termasuk grammatical dan lexical cohesion. Grammatical cohesion yang dominan muncul adalah reference. Sementara itu lexical cohesion yang dominan adalah repetition. Berdasarkan degree of cohesiveness buku ini telah memenuhi grammatical device dengan sangat baik namun secara lexical masih perlu diperbaiki lagi. Kata kunci: kohesi, grammatical cohesion, lexical cohesion, materi reading, buku pelajaran. Abstract The objective of the study is to describe the cohesion that written in the reading materials in English in Focus textbook for grade VII Junior High School both of grammatical and lexical cohesion. This study was designed as a documentary analysis in the form of descriptive qualitative research, in which the result would be described in the form of words. The result show that the reading materials in English in Focus textbook are already applied all grammatical and lexical devices. The dominant device of grammatical cohesion is reference. Meanwhile the dominant device of lexical cohesion is repetition. Based on the degree of cohesiveness this textbook has already accomplished the grammatical device very well but lexically it still needs to be improved. Keywords: cohesion, grammatical cohesion, lexical cohesion, reading text, textbook INTRODUCTION Nowadays English is one of the foreign languages that play an important for the International relationship.. Teaching English is aimed to develop students’ writing, speaking, listening and speaking skills. Recently, reading considers to be an essential skill. Reading text can be used to improve and build up reading skill of the student. Good reading skill benefits students to be able to speak well. A textbook is one of the instruments of the English teaching at school. It means that reading texts presented in the textbook should be meaningful. Although a text is made up of grammatical units (clauses, phrases, etc.), the text is not just a collection of clauses because to be text, there must be texture, created through patterns of cohesion. It is thought that students of junior high school, particularly year seven, are beginner learners of English. Therefore, they need more attention in learning this foreign language, mainly in reading class. Grammatical and lexical cohesion as the cohesive devices seems to be important in the reading text. This study is intended : (1) to describe the realization of Grammatical cohesion in “English in Focus” textbook (2) to describe the realization of Lexical cohesion in “English in Focus” textbook. RESEARCH METHODOLOGY The main objectives of this study were to describe the presentation of grammatical and lexical cohesion that written in the reading materials in the “English in Focus”. The object of the study was an English textbook for the seventh graders’ of Junior High School entitled “English in Focus” published by Departemen Pendidikan Nasional. The data of this study were all the reading materials in the reading section presented in the textbook entitled “English in Focus” for the seventh graders of Junior High School. The materials in this textbook were in the forms of texts (text with genre and short functional texts).This study was only focused on the presentation of Grammatical and Lexical Cohesion in the reading text. The data were reading materials taken from the first and second semester in the textbook. This study was designed to use descriptive qualitative on which the result of analysis is in the form of words or pictures. This study also belonged to a documentary analysis since the researcher analyzed the data or text derived from the textbook (Gerald, 1992). The researcher was the main research instrument and used checklist to help her in analyzing the data. RESULT AND DATA ANALYSIS The first research question is about how grammatical cohesion written in the textbook. The researcher found out that all of the texts are already used the grammatical cohesion but not all of the types are applied here. For example in the text 5 and text 14 there is only one aspect of grammatical cohesion is used which is conjunction, only text 12 that provides all of the type of grammatical cohesion. The researcher counted that the dominant device of grammatical cohesion utilize in the text is reference. Reference almost always appears in each text, except text 5 and text 14, consists of personal pronoun, demonstratives reference and comparative reference. It’s described on the percentage clearly that the percentage of reference exceeds almost 60 percent. The lowest percentage of grammatical aspects is ellipsis. It is just 2,4 percent. The second research question is about how the lexical cohesion written in the textbook. The researcher found out that all of the texts are used lexical cohesion although it is still lack in the quantity. Only text two that provides 2 items of collocation, the rest is just 1 item. The dominant percentage of lexical cohesion is reiteration. It is 13,2 percent. The lowest percentage is collocation, it is only 8,5 percent. All in all most of the text in the English in Focus text book already applied the cohesion but only one text that applied all of the cohesion. Beside that there are two aspects of grammatical cohesion that rarely appear in text which are substitution and ellipsis. The lexical cohesion also lack in the quantity, especially collocation. Degree of Cohesiveness shows the cohesiveness of each cohesion. The writer determines the degree of cohesiveness in the textbook through Scinto formula. From the seventeen texts above that have been analyzed by the writer, there are the differences of cohesiveness degree of grammatical and lexical cohesion Grammatical cohesion has very high level while lexical cohesion has low level. Grammatical cohesion through it’s own tools gives contribution to connect one sentence to the other sentences. The impacts of grammatical cohesion that have high level of cohesiveness degree are to ease the reader to understand the context, and the sentences are arranged well. On the other hand, lexical cohesion is still in low grade of cohesiveness degree. It builds the text become monotonous. Without development of words by some variation words can make the readers unexciting and feel bored. Based on the Irwin and Champman in Horning’s article that stated increasing the level of cohesion in the text improves reading comprehension, the English in Focus still need to add the varieties of cohesive devices. The theory from Irwin and Champman in Horning’s article that increasing the level of cohesion in the text improves reading comprehension is also need the consideration because of some reason: In the text sometimes we find that all of the text are used all of the kinds of the cohesive devices but in the low quantity. Moreover, there is also some texts that provides only few cohesive devices but in the big quantity. All in all the high level of cohesion it’s not just about how many times that the cohesive devices occurs but also about how many types of the cohesive devices are used. There is some texts that no need all of the cohesive devices in the text 5 there is only 3 types of cohesive devices are appeared because the text is advertisement and in the text 14 which is procedure text. The last is how many topic of the text that will discuss which is has the effect in the length of the text. If the text is short it is has the effect in the quantity of the cohesive devices. CONCLUSION This study aims to discover whether the reading material in English in Focus textbook ties Grammatical and Lexical Cohesion which is considered can help the students to comprehend reading better. Based on the aim, there are several conslusions that can be drawn.The first conclusion is English in Focus textbook has already applied all of the grammatical and lexical cohesion utilize in the seventeen reading texts in the preceding chapter. Through the grammatical and lexical cohesion the authors can produce the texts that can be understood well by the students because they can keep the idea tie up and cohesiveness. There is all of the grammatical cohesion stated in the seventeen texts. They are reference, ellipsis, substitution, and conjunction. The dominant device of grammatical cohesion is reference, especially personal reference. It can be seen from the percentage calculation that is stated in the chapter 4. Its percentage exceeds about fifty percent compared to the other devices. Then, the dominant lexical cohesion device is repetition. It has percentage more than fifteen percent according to the percentage calculation. The other types of lexical cohesion that appeared in the text are collocation. The cohesiveness of the texts are established because all of them are appropriately applied in those texts. The grammatical cohesion built the text grammatically whereas lexical cohesion built the text lexically. From the degree of cohesiveness it can be inferred that grammatical cohesion has high level but in the other hand lexical cohesion has very low level. In conclusion, it can be asserted that the reading materials presented in the first and second semester of English in Focus textbook were already applied all of the Grammatical and Lexical Cohesion. It is good in Grammatical, but Lexically still needs to be improved. SUGGESTION Dealing with the result of the study, some suggestions are given in this part. The suggestions are directed to the authors who compose and arrange the reading materials in the textbook entitled English in Focus, the teacher who have been or will be using the reading materials in the textbook and also the researchers who are interested in the same field of study . The suggestions are: 1. The authors who composed and arrange the reading material in English in Focus textbook; All of the Grammatical and Lexical Cohesion are already applied in this textbook but lexically still needs to be improved. The authors can increase the level of lexical cohesion in the erading text so that the students can learn a new vocabulary also. This will give the reading materials in English in Focus textbook be more suitable both for the teacher who uses it as a tool in teaching and learning process and learners who use it as a guidance in learning. 2. The teachers who have been or will be using English in Focus textbook; The teacher who have been or will be using English in Focus textbook should be more selective in choosing English textbook. They have to be capable in analyzing textbook which will be used in English teaching and learning process. However, English in Focus textbook still can be used in the class, but teacher should use an additional textbook as complement to overcome the non-conformities of English in Focus textbook. 3. Other researchers; The future researchers can be conduct a research in the other kinds of the text in this book or others. If this research only covers cohesion generally, for further analysis, people can discover more specific device of cohesion. REFERENCES Arikunto, S. 1996. Prosedur Penelitian Pendekatan Praktek. Bandung: Rineka Cipta Baker, M. 1992. In Other Words: A Course Book on Translation. London: Routledge Best, JW. 1981. Research in Education. Fourth Edition. Engelwood, USA: Prentice hall Inc Brown, J.D. 1988. Understanding Research in Second language Learning. New York: Cambridge University Press Eggins, S. 1994. An Introduction to Systemic Functional Linguistic. London: Pinter Publishers Feez, S. and Joyce, H. 1998. Text – Based Syllabus Design. Sydney: Ligare Pty Ltd Halliday, M.A.K. and Hasan, R. 1976. Cohesion in English. London: Longman Halliday, M.A.K. and Hasan, R. 1985. Language, Context, and Text, Aspect of language in Social Semiotic Perspective. Oxford: Oxford University Harmer, J. 2002. The Practice of english Language Teaching. London: Longman Horning, A. Readable Writing: The Role of Cohesion and Redudancy. http/jac.gsu.edu/jac/11.1/ articles/ g. htm (retrieved August, 9th 2006) McCarthy, M. 1991. Discourse Analysis of Language Teachers. New York: Cambridge University Press Miles, M.B and A. Michael H. 1994. Qualitative Data Analysis. London: Sage Publications Mickulecky, B. S. 1986. Reading Power. Massachussetts: Adison Wesley Publishing Company Scott, W and Ytreberg, L.H. 1990. Teaching English to Children. New York: Longman Inc Wong, R.H.K. 1974. The Educational Role and Cultural Orientation of Englsih reading Materials. http/ en.wikipedia.org/wiki/Textbook. (retrieved October, 4th 2006)